Implementasi Tanggung Jawab Kepolisian Tentang Pengamanan Eksekusi Jaminan Fidusia - Simatupang, Boby Daniel; Negoro, Wahyu Saptha; Ramadhani, Ivo (Publikasi Pengabdian Masyarakat, 2025)
In the Indonesian Government regulations, Fiduciary has been stated in Law No. 42 of 1999. Where the definition of Fiduciary is a process of transferring ownership of an object based on trust, but the object is still in the control of the party who transferred it. So that the Law becomes a means of creating a community rule that exists for everyone who wants to feel justice so that it becomes the main focus of the formation of legislation that must be in accordance with the principles of justice and the function of law as social control, then this relationship between law and social values ​​is interrelated where law as a solution to problems for society in general. Law has a dual function on the one hand is an action that may be so institutionalized which is then used by society to achieve a goal of solving problems in the responsibility of the police regarding the security of the Execution of Fiduciary Guarantees. The method used in this study is the Applied Research Method, where this method is a type of research whose results can be directly applied to solve the problems being faced. As. Prof. Mr. E.M Meyers who defines Law in his book "De Algemene bergrippen van het burglijik Recht" (Law is all rules that contain moral considerations, aimed at human behavior in society, and which serve as guidelines for state authorities in carrying out their duties). And Leon Duhuit's theory: "law is a rule of behavior for members of society, a rule whose use at a certain time is respected by a society as a guarantee of a collective reaction and which if violated will cause a collective reaction against the person who committed the violation" Problem Formulation (1). What is the attitude of vehicle owners who are still on credit in arrears in payments; (2) What needs to be prepared if you meet a Leasing Debt Collector; (3). Who has the right to carry out a fiduciary execution seizure.he abstract begins with an Indonesian